Shiva-Gauri - Temples of India Project Team (Jio Institute, 2024)
A four-armed male standing in a tribhanga posture with a female. He holds a trident in his right, and the lower left is placed around the consort's waist. The remaining hands are broken. Fluid and slender style of the body, with diaphanous clothing.